Assessing the timeliness of vaccine administration in children under five years in India, 2013. Issue 4 (21st January 2019) - Wagner, Abram L.; Shenton, Luke M.; Gillespie, Brenda W.; Mathew, Joseph L.; Boulton, Matthew L.
Highlights: A Turnbull estimator accounted for left and right censoring of vaccination dates. Maternal recall was a more common source of vaccination in India. Timeliness was 64% for DPT-1, 48% for DPT-2, and 35% for DPT-3. Accounting for left-censored data improves measures. In India, there is little increase in vaccination coverage after age one. Abstract: Morbidity from vaccine-preventable diseases is high in India, but precise estimates of vaccination timeliness are difficult to compute because many children lack records of vaccination dates. This study assessed vaccination timeliness after accounting for right and left censoring of data. This cross-sectional study used the 2012–2013 District Level Household and Facility Survey in India. The outcome was vaccination timeliness for 9 vaccine doses: 1 dose Bacillus Calmette-Guérin (BCG), 4 doses oral polio vaccine, 3 doses diphtheria-pertussis-tetanus vaccine (DPT), and 1 dose measles-containing vaccine. Age-specific probabilities of vaccination were calculated using Turnbull estimators: children not yet vaccinated were right censored, and children vaccinated but without a recorded date were left censored. Data from 108, 783 children under 5 years were available. For children 25–60 months, maternal recall was a more common source of information than a vaccination record with dates. At one month past the recommended vaccination age, estimated coverage ranged from 35% for DPT-3 to 55% for BCG. Accounting for censored data improved vaccination timeliness measures, and demonstrated little increase in vaccination coverage after age one. Efforts to reduce morbidity from vaccine-preventable diseases in India should focus on eliminating missed opportunities for vaccination and instituting special vaccination programs for older children.